2013
DOI: 10.3109/17453674.2013.842433
|View full text |Cite
|
Sign up to set email alerts
|

Revision to reverse shoulder arthroplasty with retention of the humeral component

Abstract: BackgroundRevision in failed shoulder arthroplasty often requires removal of the humeral component with a significant risk of fracture and bone loss. Newer modular systems allow conversion from anatomic to reverse shoulder arthroplasty with retention of a well-fixed humeral stem. We report on a prospectively evaluated series of conversions from hemiarthroplasty to reverse shoulder arthroplasty.MethodsIn 14 cases of failed hemiarthroplasty due to rotator cuff deficiency and painful pseudoparalysis (in 13 women)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 27 publications
5
25
0
1
Order By: Relevance
“…The most salient advantage involves reduction in the rate of periprosthetic humeral fracture during revision surgery (Figs. 6-A and 6-B) 12, 50,203,205,207 . Humeral implant design or improper stem position during the index procedure may prevent retention during revision 12, 203,207,208 .…”
Section: Evolving Trends In Shoulder Arthroplastymentioning
confidence: 99%
See 1 more Smart Citation
“…The most salient advantage involves reduction in the rate of periprosthetic humeral fracture during revision surgery (Figs. 6-A and 6-B) 12, 50,203,205,207 . Humeral implant design or improper stem position during the index procedure may prevent retention during revision 12, 203,207,208 .…”
Section: Evolving Trends In Shoulder Arthroplastymentioning
confidence: 99%
“…Raiss et al demonstrated a reduction in survivorship at 10 and 15 years after TSA performed with cement secondary to pain and implant loosening; revision procedures occurred at a mean of 8.8 years from the date of implantation 125 . The five RSA studies with minimum follow-up of 5 years noted scapular notching and instability as the most common complications 28 [33][34][35][36][37][38][39][44][45][46][47][48]50,51,53,54,[56][57][58][59]61,64,65,67,69,70,73,75,79,81,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]104,105,…”
mentioning
confidence: 99%
“…While neither group returned to full range of motion, they did achieve similar forward elevation to that previously described for revision of hemiarthroplasty to reverse total shoulder arthroplasty. 22 23) …”
Section: Discussionmentioning
confidence: 99%
“…Yet, these criteria are subjective and depend on soft-tissue impairment as well as patient relaxation. Objective techniques for postoperative assessment of deltoid tension include evaluation of the acromio-epiphyseal distance compared to the contralateral humerus [9] the difference in pre-and postoperative acromio-metaphyseal distance corrected for abduction of the arm in revision arthroplasty [16], the difference of pre-and postoperative deltoid length with respect to the greater tuberosity [17] as well as bilateral scaled radiographs of the humerus [6,18,19]. The lack of bony landmarks in case of malunion or resorption of the greater tuberosity as well as extended humeral bone defects justifies the use of the contralateral side for pre-operative planning [6] as well as postoperative assessment of lengthening.…”
Section: Discussionmentioning
confidence: 99%